Penyuluhan Penulisan Surat Lamaran Pekerjaan Dan Praktik Penulisannya Pada Siswa SMA KORPRI Banjarmasin - Shintia, Novi; Effendi, Tarman; Padli, Padli; Novyanti, Rika (Politeknik Negeri Banjarmasin, 2019)
The purpose of community service includes (1) providing information on job openings, official related information, information from advertisements, information from other sources, and without information, (2) providing information regarding how to apply for a job, especially applying for a job over the telephone and applying for a job through application letter, (3) providing information about the job application letter, especially with regard to understanding job application letters, job application letters, job application letter formats, job application letter formats , and sections of application letter, and (4) provides information on how to send application letters, application which is based on official information, information from advertisements, information from other sources, and without information. This activity was carried out on Wednesday, August 28, 2019, at the Korpri Banjarmasin High School, Jalan Tanjung I Perumnas Kayutangi Blok IV Banjarmasin. The number of students (as participants) is 20 people. Extension team of 4 people. Counseling is delivered using the lecture method, questions and answers, and the practice of receiving application letters by students. The results of the implementation issued about application letter and its practice on Banjarmasin Korpri High School students, specifically in third year students as participants, can be stated as (1) students can know well about job vacancy information, find official information, information from advertisements, information from other sources, and without information, (2) students can know well how to apply for a job, some apply for a job over the telephone and apply for a job through a job application letter, (3) students can search well for a job application letter, especially with regard to understanding job application letters, job application letter functions, formatting job application letters, and parts of job application letters, and (4) students can write job application letters with information from other sources, and without being informed Keywords: letter writing, letter form, application letter